2019
DOI: 10.3382/ps/pey378
|View full text |Cite
|
Sign up to set email alerts
|

The effects of floor space and nest box access on the physiology and behavior of caged laying hens

Abstract: Confinement housing appears to be at the forefront of concern about laying hen welfare. This experiment examined the effects of floor space during rearing (315 or 945 cm2/bird) and adulthood (542 or 1648 cm2/bird) and access to a nest box on the welfare of caged laying hens. Measurements of the normality of biological functioning, such as plasma, egg albumen and yolk and fecal corticosterone concentrations, and heterophil to lymphocyte ratios, behavioral time budgets, mortality and efficiency of productivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…There was not any significant effect linked to the four ECSs in any of the nine laying hen behaviors considered ( Table 3 ). This was also reported by Engel et al [ 44 ] who did not find any effect of litter allowance and nest-box availability on laying hen behaviors such as preening, scratching, etc., within modified cages. Other authors suggested a minimal effect on feeding, drinking, and resting behavior when space allowance is modified in furnished cages [ 45 ].…”
Section: Discussionsupporting
confidence: 85%
“…There was not any significant effect linked to the four ECSs in any of the nine laying hen behaviors considered ( Table 3 ). This was also reported by Engel et al [ 44 ] who did not find any effect of litter allowance and nest-box availability on laying hen behaviors such as preening, scratching, etc., within modified cages. Other authors suggested a minimal effect on feeding, drinking, and resting behavior when space allowance is modified in furnished cages [ 45 ].…”
Section: Discussionsupporting
confidence: 85%
“…According to previous studies, the basal level of corticosterone in laying hens ranges from 0.3 to 5 ng/ml (45), reaching 30 ng/ml in response to stress (46). The concentration of corticosterone in egg yolks has been previously reported to range from 0.77 to 2.8 ng/g in Hy-Line Brown (47)(48)(49) to an average of 1.6 ng/g in Hy-Line White (47) and 2.13 ng/g in Bovan White (50) under control conditions. The mean concentration of corticosterone in eggs from unstressed birds has been previously reported as 1.17 in yolk and 1.55 ng/ml albumen (51).…”
Section: Parent Stock: Vehicle and Cort Treatmentsmentioning
confidence: 94%
“…The welfare scoring data including the live weight, number of comb wounds, beak score, keel score, plumage score (total), and toenail length at different age points (25,33,43,56,64 weeks) throughout the laying cycle for individual hens from different rearing treatments were compiled (n = 6,876 data points/welfare parameter except for the beak score data which had n = 5,492 data points as beaks were not scored at the 25 week assessment date). The number of comb wounds and plumage score data were square-root-transformed, and the toenail length data were log 10 -transformed.…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
“…Environmental stressors can have negative impacts on the production and welfare of laying hens. Common stressors include high stocking density, changes in management practice, changes in the social environment, or changes in resource access and can result in physiological welfare impacts such as increased stress hormones and/or changes in behavioral patterns ( 19 , 22 24 ) although not in all cases ( 25 ). The impacts of these stressors may also manifest as changes in egg quality where varying parameters have been shown to be impacted by dietary corticosterone ( 26 ) or environmental stressors such as temperature and infection ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation